2005
DOI: 10.1038/sj.npp.1300667
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Ventral Striatal Dopamine Release, Cortisol Secretion, and Subjective Responses to Amphetamine

Abstract: There is evidence that stress and glucocorticoids alter drug self-administration and mesolimbic dopamine (DA) activity in preclinical models. The primary purpose of this study was to test the hypothesis that glucocorticoids are associated with psychostimulant reinforcement and DA release in humans. In total, 16 healthy adults, ages 18-27 years, underwent two consecutive 90-min PET studies with high specific activity [11 C]raclopride. The first scan was preceded by intravenous saline, and the second by intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
166
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(185 citation statements)
references
References 102 publications
15
166
2
2
Order By: Relevance
“…It is also interesting to note that alcohol cue-induced craving was only significantly associated with increases in anxiety rather than negative emotions, in social drinkers. This combination of both jitteriness and relaxed mood possibly representative of a hedonic arousal state following cue exposure, is consistent with previous research indicating that stress markers may mediate the rewarding properties of drugs (Oswald et al, 2005;Mendelson et al, 2005). Importantly, however, the emotional response to alcohol cues in the social drinkers was markedly different from the range of negative emotions reported following cue exposure in the cocaine participants.…”
Section: Discussionsupporting
confidence: 89%
“…It is also interesting to note that alcohol cue-induced craving was only significantly associated with increases in anxiety rather than negative emotions, in social drinkers. This combination of both jitteriness and relaxed mood possibly representative of a hedonic arousal state following cue exposure, is consistent with previous research indicating that stress markers may mediate the rewarding properties of drugs (Oswald et al, 2005;Mendelson et al, 2005). Importantly, however, the emotional response to alcohol cues in the social drinkers was markedly different from the range of negative emotions reported following cue exposure in the cocaine participants.…”
Section: Discussionsupporting
confidence: 89%
“…We previously demonstrated during PET imaging in humans that AMPH-induced DA release is correlated with AMPH-induced cortisol secretion as well as with positive subjective drug responses including drug 'liking,' 'desire,' 'good effect,' 'high,' and 'rush' (Oswald et al, 2005). However, the prior study did not clarify whether cortisol responses to a psychological stressor would also be associated with DA responses to AMPH.…”
Section: Introductionmentioning
confidence: 55%
“…All participants provided written informed consent under the oversight of The Johns Hopkins School of Medicine Institutional Review Board. Sixteen of the subjects were included in our first PET study that examined the relationship between AMPH-induced cortisol vs AMPH-induced DA release (Oswald et al, 2005). Subject assessment included a medical history and physical exam performed by a physician, complete blood count, comprehensive metabolic panel (including renal and hepatic function tests), electrocardiogram, urinalysis, alcohol breathalyzer test, and urine toxicology screen.…”
Section: Screening Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled studies in humans have shown that acute administration of low AMPH doses produces subjective effects like euphoria, 'mind racing', and alertness Angrist, 1987;McTavish et al, 1999;Vollm et al, 2004); physiological changes in heart rate and blood pressure have also been monitored (Griffith and Gunne, 1977;Brown et al, 1978;Angrist et al, 1987;Angrist, 1987;Cook et al, 1993;Oswald et al, 2005). In many of these studies, when the time course of these stimulant-induced alterations was determined, a dissociation between these effects and measured or inferred plasma levels was apparent and often referred to as acute tolerance or tachyphylaxis Angrist, 1987;Cook et al, 1993;Swanson et al, 2002;Greenhill et al, 2003;Foltin and Haney, 2004).…”
Section: Behavioral Profilementioning
confidence: 99%